The Influence of organizational learning capability on success of technological innovation (Product) implementation with moderating effect of knowledge complexity - Razli Che Razak; Adam Mat (2011)
The purpose of this proposed framework paper is to explore the relationship between organizational learning capability, knowledge complexity and their impact on technological innovation (product) implementation success. Research has fairly established that technological innovation implementation is associated with organizational learning. However, few studies have investigated on the roles of knowledge complexity on the established relationship. This paper will focuses at implementation phase of innovation process, where innovation has be fully developed then it must be implemented. Identification of success or failure of innovation can be done through implementation phase. This paper aims to investigate the framework knowledge complexity as moderating effect on the relationship between organizational learning capability and technological innovation (product) implementation.